Evolving Approach in Hypoplastic Left Heart Syndrome With Restrictive and Intact Septum. Issue 3 (May 2022) - Generali, Tommaso; Hermuzi, Antony; Sajnach-Menke, Magdalena; Johnson, Anna; Crossland, David S.; O'Sullivan, John J.; Nassar, Mohamed; Hasan, Asif; De Rita, Fabrizio
Background: Hypoplastic left heart syndrome (HLHS) with either intact atrial septum (IS) or highly restrictive interatrial communication (HRIC) is associated with poor survival. Immediate postpartum access to cardiac therapy and timely left atrial decompression (LAD) are paramount to a successful outcome. We describe herein our evolving approach to LAD and report interstage and longer-term results.Methods: We retrospectively identified neonates with HLHS IS/HRIC requiring LAD between 2005 and 2019. All babies had prenatal/postnatal echocardiography. Our LAD strategy evolved over time from attempt at transcatheter balloon atrial septostomy (BAS) to surgical septectomy with inflow occlusion, to hybrid trans-atrial stent implantation.Results: Twelve neonates required LAD at a median time of 14 (0.5-31) hours after birth. Five patients underwent BAS that proved successful in 2 cases. Of the 3 unsuccessful cases, 2 required extra-corporeal membrane oxygenation (ECMO) support and died subsequently; one underwent hybrid trans-atrial stent implantation. Of the remaining 7 patients, 3 underwent surgical septectomy with inflow-occlusion and 4 underwent hybrid trans-atrial stent implantations. Overall, 8 patients survived LAD and reached Norwood palliation. Three of the 8 required ECMO postoperatively. There was no hospital mortality after Norwood stage 1 palliation and interstage survival was 100%. Six patients successfully underwent Glenn shunt (superior cavopulmonary anastomosis) and 5 have completed total cavopulmonary connection.Conclusions: Our experience suggests that prompt postnatal LAD can be safely achieved with careful multidisciplinary planning and accurate antenatal diagnosis. In our hands, hybrid trans-atrial septal stent insertion appears to be a safe approach which combines the versatility of transcatheter techniques together with the effectiveness of surgical control.